CHALLENGES AND OPPORTUNITIES OF LEARNING ENGLISH AS A FOREIGN LANGUAGE (Ustozlar uchun, 2025)
Abstract: This paper explores the major challenges and opportunities faced bylearners of English as a foreign language (EFL). It discusses linguistic, psychological, andcultural barriers, as well as the growing opportunities provided by globalization and digitaltechnology. The study is based on qualitative research through classroom observation andlearner interviews. Findings show that although EFL learners face difficulties related topronunciation, motivation, and limited exposure, technology, intercultural communication,and modern teaching approaches can significantly enhance their learning outcomes.